The Effect of Counseling on Improving Knowledge, Attitude, and Behavior in Efforts to Prevent and Control Non-Communicable Diseases (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2019)
Non-communicable diseases in Bengkulu Province has been increasing from 2007 to 2013. Integrated non-communicable disease development post (Posbindu PTM) is a platform for community participation in early detection and monitoring of risk factors in an integrated and periodic manner. Counseling on Posbindu PTM activities is one of the factor that could improve knowledge, attitude and behavior towards prevention and control of non-infectious diseases (NCDs). The study aimed to investigate the influence of counseling on the improvement of knowledge, attitude and behavior towards NCDs prevention and control. Through a quantitative research with quasi-experimental design, counseling at Posbindu PTM Damai and Padang Harapan Kota Bengkulu was conducted. The population and samples were all 32 members of Posbindu PTM. We found a difference in knowledge, attitude, and behavior before and after counseling from dependent and independent t-test analysis. The Community Health Centers (Puskesmas) need to train their cadres so that they are capable to counsel Posbindu PTM members to improve their knowledge, attitudes, and behavior towards prevention and control of NCDs.